(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
This article explores the historical and archaeological significance of the Teshiktepa and Chinortepa monuments located in the Uzun district of Uzbekistan. It provides an overview of recent excavations, findings, and scholarly interpretations related to these ancient sites. Special attention is given to the cultural layers, artifacts, and architectural structures uncovered, which shed light on the region’s role in the socio-economic and cultural development of early civilizations in Central Asia. The study also highlights the importance of preserving and further investigating these sites for understanding the broader historical landscape of the region.